The peculiarities of organization of student’s self-training the peculiarities of organization of student’s self-training workwork - Бондар, Л.В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2012)
The student’s abilities of making of self-training work as substantial analysis, generalization and application of it as a ways of educational activity are studied in the article.